Assessment of occupational risks in the Ecuadorian dairy industry. - Mayerli Angeline,; Velásquez Avilés, Carlos Alberto; Viteri García, Ivan Patricio (Ingeniería Química y Desarrollo, 2026)
This review draws on sixty sources published between 2013 and 2025 to assess how dairy plants manage occupational hazards, paying special attention to Latin American—and especially Ecuadorian—settings. Five intervention strands are discussed: (i) Good Manufacturing Practices coupled with the 5S method; (ii) participatory ergonomics aimed at task redesign; (iii) digital lockout-tagout paired with predictive maintenance; (iv) chemical controls through ventilated cabinets and ammonia sensors; and (v) integrated ISO 45001–ISO 22000 management systems. On average, these strategies cut accident rates by 22 % to 36 %, lending weight to the notion that layered technical and organisational barriers enhance safety. Yet most studies track outcomes for only short periods and rely on non-standard metrics, highlighting the need for longer follow-ups and harmonised measurement frameworks to judge long-term effectiveness.
Keywords: Dairy Occupational Safety; Good Manufacturing Practices; 5S; Participatory Ergonomics; Digital Lockout-Tagout; Predictive Maintenance; Chemical Management; ISO 45001; ISO 22000